Benign metastasizing leiomyoma in retroperitoneal lymph nodes with concurrent early stage cervical cancer - Danielle Glassman; Jharna M. Patel; Lara Hathout; Sumi Thomas; Eugenia Girda (Elsevier, 2022)
Extrauterine leiomyomas can present as benign metastasizing leiomyoma involving lymph nodes, which can be mistaken for metastatic malignancy. We report a case of a 52-year-old female who presented with postmenopausal bleeding and was found to have an endocervical mass. Imaging demonstrated retroperitoneal lymphadenopathy and biopsy of the cervical mass showed adenocarcinoma of either uterine or cervical origin. Patient underwent hysterectomy, bilateral salpingo-oophorectomy and lymphadenectomy for bulky pelvic and para-aortic lymph nodes. Final pathology was consistent with FIGO 2019 stage IB2 adenocarcinoma of the cervix with concurrent and benign metastasizing leiomyomas involving retroperitoneal lymph nodes.